Effect of a magnetic field on stress corrosion cracking of Fe83Ga17 alloy. (1st May 2020) - Zhao, S.L.; Bai, J.J.; You, Z.F.; Li, J.X.
Highlights: The effect of a magnetic field on the SCC of Fe83 Ga17 alloy was studied for the first time. A parallel magnetic field inhibited pitting corrosion. Different directions of applied magnetic field resulted in diverse forms for the V-groove corrosion. Mechanism of crack corrosion under different directions of magnetic field was proposed. Abstract: As a new magnetostrictive material, Fe-Ga alloy has been used in ships as a displacement sensor. Therefore, it is necessary to study its corrosion and stress corrosion cracking (SCC). This research is the first report of the effect of a magnetic field on the SCC of Fe83 Ga17 alloy by slow strain rate tensile (SSRT) tests. The results showed that a parallel magnetic field reduced pitting corrosion. The effect of a magnetic field on V-groove corrosion was different in the different directions. Further, the SCC of Fe83 Ga17 alloy was enhanced with a tensile magnetic field and was inhibited with an in-plane or a perpendicular magnetic field.